2019
DOI: 10.3390/vision3030035
|View full text |Cite
|
Sign up to set email alerts
|

Regressions during Reading

Abstract: Readers occasionally move their eyes to prior text. We distinguish two types of these movements (regressions). One type consists of relatively large regressions that seek to re-process prior text and to revise represented linguistic content to improve comprehension. The other consists of relatively small regressions that seek to correct inaccurate or premature oculomotor programming to improve visual word recognition. Large regressions are guided by spatial and linguistic knowledge, while small regressions app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…This may seem like an intentional feature of RAP, since the prevention of regressions will inevitably lead to higher reading rates. However, regressions are often crucial to achieve sufficient levels of text comprehension and do not necessarily indicate low levels of reading proficiency (Inhoff et al., 2019). A technical solution for this problem might be a stop button, which pauses the fader and triggers the reappearance of the text, allowing the reinspection of a passage until the stop button is released.…”
Section: Conclusion—limitations and Benefitsmentioning
confidence: 99%
“…This may seem like an intentional feature of RAP, since the prevention of regressions will inevitably lead to higher reading rates. However, regressions are often crucial to achieve sufficient levels of text comprehension and do not necessarily indicate low levels of reading proficiency (Inhoff et al., 2019). A technical solution for this problem might be a stop button, which pauses the fader and triggers the reappearance of the text, allowing the reinspection of a passage until the stop button is released.…”
Section: Conclusion—limitations and Benefitsmentioning
confidence: 99%
“…), the idea to summarize all regressions under one unifying function is probably not convincing. Inhoff et al [ 1 ];, for example, suggested that two different types of regressions can be distinguished, namely according to their size, function and target control. One type is referred to as ‘large regressions’ and comprises regressions “that traverse across more than one prior word” (p. 36).…”
Section: A New Approach: the Information Gathering Frameworkmentioning
confidence: 99%
“…On the one hand, regression target locations show a more complex distribution pattern (see e.g. Inhoff et al, 2019, for a review) and on the other hand, post-lexical integration difficulties cannot account for all types of regressions (see e.g. the function of 'small regressions' proposed by Inhoff et al, 2019, or the socalled 'sentence wrap-up effects' mentioned earlier).…”
Section: E-z Reader 10mentioning
confidence: 99%
See 2 more Smart Citations